2010
DOI: 10.1111/j.1365-3156.2010.02627.x
|View full text |Cite
|
Sign up to set email alerts
|

High failure rate of the dissolution tests for 500-mg amoxicillin capsules sold in Cambodia: is it because of the product or the test method?

Abstract: Summaryobjectives During the survey of substandard medicines in Cambodia in 2007, it was found that more than 90% of 500-mg amoxicillin (AMPC) capsules failed the United States Pharmacopeia (USP) 30 TEST 1 dissolution test. In the USP, several monographs provide multiple methods for performing the dissolution test. By using the 500-mg AMPC capsule as an example, we aimed to identify the problems and implications of the USP methods adopted for the dissolution test as a global standard. results All 500-mg AMPC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…There were 5 in vitro comparative dissolution studies conducted in an aqueous medium according to pharmacopeial methods. The first study, on 35 quality-tested amoxicillin 500 mg capsule products sold in Cambodia, used USP 30 TEST 1, USP 30 TEST 2, and USP 28 methods and showed a high-dissolution failure rate with respect to USP 30 TEST 1 91 (with a pass rate of only 8.6%). By contrast, the pass rate with the USP 30 TEST 2 was 97.1%, and with the USP 28 test, it was 97.1%.…”
Section: Comparative Dissolution Studies Of Amoxicillin Products Usinmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 5 in vitro comparative dissolution studies conducted in an aqueous medium according to pharmacopeial methods. The first study, on 35 quality-tested amoxicillin 500 mg capsule products sold in Cambodia, used USP 30 TEST 1, USP 30 TEST 2, and USP 28 methods and showed a high-dissolution failure rate with respect to USP 30 TEST 1 91 (with a pass rate of only 8.6%). By contrast, the pass rate with the USP 30 TEST 2 was 97.1%, and with the USP 28 test, it was 97.1%.…”
Section: Comparative Dissolution Studies Of Amoxicillin Products Usinmentioning
confidence: 99%
“…By contrast, the pass rate with the USP 30 TEST 2 was 97.1%, and with the USP 28 test, it was 97.1%. 91 The second study, conducted with 9 generic brands of amoxicillin 500 mg capsules as well as the innovator product, was carried out according to USP 32, and the interchangeability was gauged by calculating difference and similarity factors. This study found only 2 brands which could show a difference factor (f 1 ) less than 15 and only 1 brand out of 9 which had a similarity factor (f 2 ) more than 50, indicating that most brands did not behave similarly to the innovator product.…”
Section: Comparative Dissolution Studies Of Amoxicillin Products Usinmentioning
confidence: 99%
“…The poor dissolution rates of the samples were a persistent problem, an observation which had previously been reported in our studies [56,57,60,61]. As an essential indicator of bioavailability and drug quality, the dissolution test has not been given as much attention as it deserves [58,62,63]. Despite the fact that all of the ESM samples contained the stated amount of API, a poor dissolution rate was observed in the buffer stage of the dissolution test in 10.9% of the ESM samples (Table 3; Figs.…”
Section: Discussionmentioning
confidence: 49%
“…The ineffectiveness of these formulations could easily result in treatment failure. Drug dissolution testing is still being considered to be a minimal requisite in many pharmaceutical quality studies, given that the dissolution testing is one of the key parameter to observe the physicochemical changes in a solid formulation [47]. This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%